Differential Gray Matter Vulnerability in the 1 Year Following a Clinically Isolated Syndrome - Koubiyr, Ismail; Deloire, Mathilde; Coupé, Pierrick; Dulau, Cécile; Besson, Pierre; Moroso, Amandine; Planche, Vincent; Tourdias, Thomas; Brochet, Bruno; Ruet, Aurélie (Frontiers in Neurology, 2018)
Background and purpose: Whether some gray matter (GM) regions are differentially vulnerable at the early stages of MS is still unknown. The objective of this study is to investigate whether deep and cortical GM are differentially vulnerable after a clinically isolated syndrome (CIS) suggestive of multiple sclerosis (MS). Methods: Fifty-six patients with CIS (PwCIS) and 38 healthy controls (HC) had conventional and diffusion tensor imaging (DTI) at baseline and 46 PwCIS and 20 HC were rescanned after one year. Deep GM (DGM) volumes, cortical thickness (CTh) and DTI metrics (FA: fractional anisotropy; MD: mean diffusivity) within these structures were calculated for each participant at each time-point and compared between PwCIS and HC. Linear regression models were used to investigate whether baseline DTI parameters could predict GM volume loss over time. Results: At baseline, GM volumes did not differ between PwCIS and HC, but hippocampal MD was higher in PwCIS than HC (p<0.01). Over one year, GM alterations became more widespread with putamen and hippocampus volumes decreasing in PwCIS (p<0.01), and cortical thinning in different parts of the cortex along with a significant increase of MD. Hippocampus MD at baseline could predict its volume loss (R2=0.159; p<0.05) and cortical thinning was associated to microstructural damage (Spearman’s rho ranging from -0.424 to -0.603 with p<0.003). Conclusion: Along with MS being a diffuse inflammatory disease, GM showed a differential vulnerability at the early stage spreading from hippocampus to the cortex. Hippocampus volume loss could be predicted by its MD at baseline.